Experimental Characterization of the Hepatitis B Virus Capsid Dynamics by Solid-State NMR - Malär, Alexander A.; Callon, Morgane; Smith, Albert A.; Wang, Shishan; Lecoq, Lauriane; Pérez-Segura, Carolina; Hadden-Perilla, Jodi A.; Böckmann, Anja; Meier, Beat H. (Frontiers in Molecular Biosciences, 2022)
Protein plasticity and dynamics are important aspects of their function. Here we use solid-state NMR to experimentally characterize the dynamics of the 3.5 MDa hepatitis B virus (HBV) capsid, assembled from 240 copies of the Cp149 core protein. We measure both T1 and T1𝜌 relaxation times, which we use to establish detectors on the nanosecond and microsecond timescale. We compare our results to those from a one microsecond all-atom Molecular Dynamics (MD) simulation trajectory for the capsid. We show that, for the constituent residues, nanosecond dynamics are faithfully captured by the MD simulation. The calculated values can be used in good approximation for the NMR-non-detected residues, as well as to extrapolate into the range between the nanosecond and microsecond dynamics, where NMR has a blind spot at the current state of technology. Slower motions on the microsecond timescale are difficult to characterize by all-atom MD simulations owing to computational expense, but are readily accessed by NMR. The two methods are, thus, complementary, and a combination thereof can reliably characterize motions covering correlation times up to a few microseconds.